Biomass Wastes for Energy Production - Monteiro, Eliseu (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Environmental problems are forcing a rethinking of the world's energy supply system. In parallel, there is an increasing amount of global solid waste production. A fundamental shift toward greater reliance on biomass wastes in the world's energy system is plausible because of ongoing major technological advances that hold the promise of making the conversion of biomass into high-quality energy carriers, like electricity and gaseous or liquid fuels, economically competitive with fossil fuels. Therefore, waste-to-energy systems have become a paramount topic for both industry and researchers due to interest in energy production from waste and improved chemical and thermal efficiencies with more cost-effective designs. This biomass shift is also important for industries to become more efficient by using their own wastes to produce their own energy in the light of the circular economy concept. This book on "Biomass Wastes for Energy Production" brings novel advances on waste-to-energy technologies, life cycle assessment, and computational models, and contributes to promoting rethinking of the world's energy supply systems.